Reformed theology in dialogue with a spirituality of creation within the context of religious pluralism in Africa - Knoetze, Johannes J. (HTS teologiese studies, 2021)
A transforming spirituality is needed to attend to the ‘third-millennial needs’ of Africa to address issues such as relationships (tribal wars, genocide, ISIS, etc.), globalisation ([new]-colonisation and urbanisation), ecology (industrialisation and rhino or elephant poaching) and social issues (the poor, women and children). It is argued that reformed theology, African spiritualities and a spirituality of creation need to be enriched by each other to bring about transformation in Africa. To discover a transforming spirituality of creation, participants need to listen to the different spiritualities and beliefs, without attempting to create a meta-narrative. Participants need to acknowledge the differences and even tensions, and embrace these. As such, this article attends to the research question, how can a dialogue between reformed theology and spirituality of creation help to establish a transforming spirituality based on common values for the diverse African continent in ‘our third-millennial world’?Contribution: From a multidisplinary theological perspective, the article deals with ‘historical thought’ regarding spirituality and creation. This includes both the textual history from Christianity and oral history from Africa. A missional hermeneutics is used to bring different traditions and beliefs together.